Strategi Komunikasi dalam Keluarga Antar Suku Jawa-Dayak di Kota Palangka Raya - Junaidi Junaidi; Aquarini Aquarini; Nauliana Nauliana (​Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2019)
Communication Strategy is planning and management for a purpose with effective communication in it. This research will explain and describe the Communication Strategies in the Java-Dayak Family in the City of Palangka Raya. The study entitled